The Electronic Health Record and Nursing Practice. Issue 2 (March 2016) - McCartney, Patricia Robin
Abstract : The electronic health record has an impact on all aspects of nursing practice. Our HIT nursing expert, Dr. McCartney offers advice on how to take action to promote safe use of the electronic health record.